Recovery of coefficients for a weighted p-Laplacian perturbed by a linear second order term. (17th December 2020) - Cârstea, Cătălin I; Kar, Manas
Abstract: This paper considers the inverse boundary value problem for the equation ∇ ⋅ ( σ ∇ u + a |∇ u | p −2 ∇ u ) = 0. We give a procedure for the recovery of the coefficients σ and a from the corresponding Dirichlet-to-Neumann map, under suitable regularity and ellipticity assumptions.